2014
DOI: 10.1586/14737167.2015.972379
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of adjuvant chemotherapy in patients with stage III colon cancer in Thailand

Abstract: The adjuvant FOLFOX and FOLFIRI as the first-line treatment for metastatic disease would be cost-effective with an incremental cost-effectiveness ratio of 299,365 Thai baht per QALY gained based on a societal perspective if both prices of FOLFOX and FOLFIRI were decreased by 40%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In the remaining study, the cost of capecitabine acquisition was reported as almost 10 times the cost of 5-FU, which is substantially higher than reported in other studies. 32 Notably, there was no full evaluation comparing capecitabine to 5FU in stage II CRC.…”
Section: Ac Vs No Acmentioning
confidence: 99%
See 2 more Smart Citations
“…In the remaining study, the cost of capecitabine acquisition was reported as almost 10 times the cost of 5-FU, which is substantially higher than reported in other studies. 32 Notably, there was no full evaluation comparing capecitabine to 5FU in stage II CRC.…”
Section: Ac Vs No Acmentioning
confidence: 99%
“…15 Amongst stage III studies, 7 of 8 (88%) full economic evaluations determined that FOLFOX was cost-effective compared to 5-FU alone. 22,26,30,32,34,[39][40][41][42][43] The remaining study modelled strategies that included different treatments for metastatic recurrence, limiting the assessment of AC alone. 32 Additionally, Pandor et al concluded that FOLFOX dominates capecitabine in stage III.…”
Section: Oxaliplatin-based Acmentioning
confidence: 99%
See 1 more Smart Citation
“…prolong survival of the patients; nevertheless, the mortality and morbidity of the disease are high. Moreover, colonic cancer treatment costs become higher than in the past due to development of new-targeted therapies (Faivre, 1994;Lerdkiattikorn et al, 2015). Prevention can be one of the most cost-effective measures for low resources countries such as Thailand (Khuhaprema and Srivatanakul, 2008;Lepage et al, 2010).…”
Section: Modifiable Factors and Colon Cancer Risk In Thai Populationmentioning
confidence: 99%
“…Moreover, decision makers' work nowadays is likely to be more difficult than it was 50 years ago, when only one or a few treatment choices were available for each disease and at relatively low cost. For example, only one option was available for adjuvant therapy for stage III colon cancer in 1989 [2], but there are now nine choices in the recent evaluation, of which the most expensive treatment regimen has a medicine price that is 32 times higher than the least expensive alternative [3].…”
mentioning
confidence: 99%